Development of an Entrepreneurship Training Model for Student in the Liuzhou Institute of Technology - Wenjun, Xiao; Singkhleewon, Nutdanai; Teekasap, Sombat; Phokheaw , Sirigarn (วารสารวิชาการเทคโนโลยีอุตสาหกรรม มหาวิทยาลัยราชภัฏสุรินทร์, 2024)
In the wave of the new technological revolution, leaders in the technology innovation industry will steer the direction of future development. The realization and application of technological innovation is closely linked to the cultivation and development of talent. Entrepreneur training models play a crucial role in universities, as they not only help cultivate students' entrepreneurial spirit and enhance their innovation capabilities and practical competencies but also provide vital support for their development in new technological fields. This study focuses on Liuzhou Institute of Technology as the research subject, to identify and develop an entrepreneur training model. Through in-depth interviews with 9 industry experts and evaluations by an additional 21 experts, the key elements of the model, including 9 main elements and 66 sub-elements, were identified. The findings contribute to a deeper understanding of the composition of entrepreneur training models, providing guidance for universities in training talent with innovative thinking and entrepreneurial skills, thus promoting the cultivation and development of students' innovation and entrepreneurial abilities.